Español: un análisis ordinal con enfoque hacia carreras de ciencia y tecnología (Revista Peruana de Investigación Educativa, 2020)
The objective of this paper is to explain labor market mismatch in recently university graduates of Science, Technology, Engineer and Mathematics (STEM) careers through the National Survey on University Graduates and Universities 2014. We distinguish two types of labor mismatch: minor and major. In general, 60.7 percent of graduates are in labor market mismatch, being bigger in STEM workers than in non-STEM workers. However, most STEM workers are in minor mismatch, while  the opposite phenomenon occurs in non-STEM workers.  For assessing its determinants We use a Partial Generalized Ordinal Logit (PGOL) model. The results show that family characteristics and the way how education was imparted have a significant effect on the probability of being in labor market mismatch.